MEDIA PEMBELAJARAN RAMBU LALU LINTAS DENGAN MENERAPKAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Jeffry Sugiarto; Indah Dwi Mumpuni; Ali Syaifulloh (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
One of the traffic problems that occur is the violation of traffic signs or signs that have increased from year to year. So that the introduction of traffic signs should be done early. Then the merging of interactive quizzes with Augmented Reality (AR) technology can be used as a solution as a learning media application for the introduction of Android-based traffic signs to elementary school students. In this application there is an introduction to traffic signs using AR technology, in addition there is also a quiz menu that contains questions about traffic signs to measure the level of understanding of elementary school students. This application can be run on Android smartphone devices with RAM specifications of 1GB and above and version 4.1 (Jelly Bean) and above. The results of the application testing that has been done at SDN 2 Tirtomoyo Pakis that the application can increase student understanding, as evidenced by the results of the pretest and posttest tests on students experiencing an increase in the average value of understanding from 79.66 to 92.76. This application is also considered interesting and interactive, this can be proven from the criteria tested that the application is easy to use, the application is interesting, understand after using the application and fun / not boring the result is 32% said agree and 61% said strongly agree. So it can be concluded that the Rambutaan application is interesting and interactive.